Detection and perception of generic host volatiles by mosquitoes: responses to CO2 constrains host-seeking behaviour. Issue 5 (10th May 2017) - Majeed, Shahid; Hill, Sharon Rose; Dekker, Teun; Ignell, Rickard
Abstract : Natural selection has favoured specialization in anthropophilic mosquito host choice, yet in the absence of human hosts, females feed on a selected range of vertebrates. For host recognition, we hypothesize that mosquitoes primarily rely on generic host volatiles. Detection and perception of such compounds would provide the mosquito with a flexible, yet constrained, odour coding system that could delineate host preference. In this study, we show that the quintessential generic volatile for host-seeking, carbon dioxide, activates and attracts the malaria mosquito, Anopheles coluzzii, and the arbovirus vectors, Aedes aegypti and Culex quinquefasciatus, within boundaries set by the dynamic range and coding capacity of the CO2 -sensitive olfactory receptor neurons. These boundaries are sufficiently broad to elicit behavioural responses to various hosts within their preferred host range. This study highlights the significance of the sensitivity of the carbon dioxide detection system and its regulation of host seeking and recognition.